Pengaruh upah minimum, pertumbuhan ekonomi dan pendididikan terhadap penyerapan tenaga kerja di Provinsi Sumatera Selatan - Dirta Pratama Atiyatna; Nurlina T. Muhyidin; Bambang Bemby Soebyakto (Jurnal Ekonomi Pembangunan, 2016)
The purpose of this research is to analyze the effect of minimum wage, economic growth and education in South Sumatera from 1995-2014 using secondary data. This study uses quantitative and qualitative analytical techniques in which multiple regression and dummy variables are used in the quantitative methods. The dummies used are (1) education below high school and (2) education above high school. The results show that minimum wage and variable dummy (1) have significant effect on the labor absorption during the observation period. There is positive association in both of variables on labor absorption in which labor absorption increases as minimum wage and variable dummy (1) increases. Meanwhile, multicollinearity occurs when economic growth added, therefore it is eliminated from the model. Variabe dummy (1) is significantly more influential compare to variable dummy (2) indicating higher labor absorption in elementary (SD) and junior high school (SMP) education